Adenine as an organocatalyst for the ring-opening polymerization of lactide: scope, mechanism and access to adenine-functionalized polylactide. Issue 5 (7th July 2016) - Nogueira, Guilherme; Favrelle, Audrey; Bria, Marc; Prates Ramalho, João P.; Mendes, Paulo J.; Valente, Andreia; Zinck, Philippe
Abstract : Straightforward access to a bioconjugate is reported via adenine initiated ring-opening polymerization without a co-catalyst. The mechanism is elucidated by DFT. Abstract : Nucleobase-functionalized polymers are widely used in the fields of supramolecular chemistry and self-assembly, and their development for biomedical applications is also an area of interest. They are usually synthesized by tedious multistep procedures. In this study, we assess adenine as an organoinitiator/organocatalyst for the ring-opening polymerization of lactide.l -Lactide can be quantitatively polymerized in the presence of adenine. Reaction conditions involving short reaction times and relatively low temperatures enable the access to adenine end-capped polylactide in a simple one-step procedure, in bulk, without additional catalyst. DFT calculations show that the polymerization occurs via hydrogen bond catalysis. The mechanism involves (i) a hydrogen bond between the NH9 of adenine and the carbonyl moiety of lactide, leading to an electron deficient carbon atom, and (ii) a second hydrogen bond between the N3 of adenine and the NH2 of a second adenine molecule, followed by a nucleophilic attack of the latter activated amine on the former electron deficient carbon on the monomer. For longer reaction times and higher temperatures, macrocyclic species are formed, and a mechanism involving the imidazole ring of adenine is proposed based on literature studies. Depending on the reaction conditions, adenine can thus be considered as an organoinitiator or an organocatalyst for the ring-opening polymerization of lactide.